DAMPAK DIABETES MELITUS PADA USIA PRODUKTIF - Chudri, Juni; Sudarma, Verawati; Handayani, Astri; Chondro, Fransisca (Jurnal Pengabdian Masyarakat Trimedika, 2024)
Diabetes Mellitus (DM) is the  most common metabolic diseases and can cause complication. This disease can cause complaints regarding microcirculation and macrocirculation as well as sarcopenia, which can interfere the capability in performing daily activities. This community service were carried out on 100 respondents using the counseling method and Body Mass Index (BMI) was measured for each participants. The results obtained were 12% of the respondent were underweight, 17% respondents have normal BMI, 19% were overweight, 31% have obesity type 1 and 21% respondents have type 2 obesity. As for the knowledge there was an increased in the average score of knowledge from 4.5 in the pretest  to 6.3 for the average post test score